Prisoners' Obligations to Provide Support for Their Family According to Islamic Law and Positive Law - Jamarudin, Ade; Ch Pudin, Ofa; Said, Muh.; Hidayatullah, Ahmad Firman; Syafi’ah, Syafi’ah (Universitas Islam Negeri Raden Intan Lampung, 2023)
A husband, in his position as head of the household, is obliged to provide the best possible living for his wife and children and provide for them according to his ability. On the other hand, a wife, in her position as a housewife, is obliged to manage the internal affairs of the household, starting from raising and caring for children, and providing food, to maintaining family assets. The wife is not responsible for the family economy, but she can play a role in earning a living for the family with her husband's permission. This research aims to examine the provisions of Islamic law and positive law towards prisoners who cannot carry out their duties to provide support for their families. This type of research includes normative juridical research using data collection techniques in the form of literature studies. The research found that prisoners generally cannot provide a living for their families. Therefore, they are forced to entrust their wife and children to their families or to transfer previous business to the wives, allow their wives to earn a living, and even allow them to divorce and remarry. To overcome this problem, it is hoped that the Government can develop the function of Penitentiary Institutions by creating independent employment opportunities for prisoners so that they can earn income to help ease the burden on their families.